Does an optimal relationship between injury risk and workload represented by the "sweet spot" really exist? An example from elite French soccer players and pentathletes - Sedeaud, A.; De Larochelambert, Q.; Moussa, I.; Brasse, D.; Berrou, J.-M.; Duncombe, S.; Antero, J.; Orhant, E.; Carling, C.; Toussaint, J.-F (Frontiers in Physiology, 2020)
Objective: To examine the relationships between the occurrence and severity of injuries using three workload ratios (ACWR, EWMA, REDI) in elite female soccer players and international male and female pentathletes.